Constructed Women: Gender Performativity and the Male Gaze in Alfred Hitchcock’s Vertigo (1958) - Kamila, Ananda Cahya; Maulidya, Reza Anis (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
Alfred Hitchcock’s Vertigo (1958) presents a powerful exploration of how gender identity is constructed through social control, visual surveillance, and patriarchal desire. Using Judith Butler’s theory of gender performativity and feminist film theory, the film reveals femininity not as an innate truth but as a repeated performance shaped by societal norms. Scottie Ferguson’s obsessive transformation of Judy Barton into Madeleine Elster becomes a metaphor for the coercive forces that dictate how women should appear and behave. Cinematic elements such as costume, mirrors, spirals, and the male gaze illustrate the ways in which female identity is molded, fragmented, and objectified. Judy’s psychological distress and eventual death expose the emotional cost of being forced to perform a role that erases the self. The film’s visual repetition and symbolic motifs underscore the instability of gender identity and the violence of imposed norms. Rather than offering closure, Vertigo leaves viewers with a critique of gender expectations and a reflection on the fragile nature of identity. Through its narrative and visual language, the film challenges fixed categories of gender and remains deeply relevant to discussions of power, control, and resistance in cultural representation. Keywords: Gender Performativity, Feminist Film Theory, Alfred Hitchcock, Vertigo